2005
DOI: 10.1103/physrevlett.94.054503
|View full text |Cite
|
Sign up to set email alerts
|

Four Sided Domains in Hierarchical Space Dividing Patterns

Abstract: The cracks observed in the glaze of ceramics form networks, which divide the 2D plane into domains. It is shown that, on the average, the number of sides of these domains is four. This contrasts with the usual 2D space divisions observed in Voronoi tessellation or 2D soap froths. In the latter networks, the number of sides of a domain coincides with the number of its neighbors, which, according to Euler's theorem, has to be six on average. The four sided property observed in cracks is the result of a formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
45
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 13 publications
(18 reference statements)
8
45
0
Order By: Relevance
“…In the case of a stiff substrate this interaction distance is on the order of the thickness of the coating. Such familiar hierarchical disordered patterns are for instance observed in dry mud [8,9], in the glaze of ceramics or even in plant venation and urban networks [10]. Delamination may eventually occur after the previous fracture pattern has been established [11].…”
mentioning
confidence: 99%
“…In the case of a stiff substrate this interaction distance is on the order of the thickness of the coating. Such familiar hierarchical disordered patterns are for instance observed in dry mud [8,9], in the glaze of ceramics or even in plant venation and urban networks [10]. Delamination may eventually occur after the previous fracture pattern has been established [11].…”
mentioning
confidence: 99%
“…The stress field around the crack tip is then modified by the presence of the other cracks leading to kinked trajectories. In hierarchical fracturing processes [13], it is usually observed that cracks coalesce around a 90°angle, as for example in dessication [14][15][16] or in fault dynamics [17][18][19][20]. It has also been shown that two collinear approaching cracks (submitted to a uniaxial stress in mode I) can repel each other instead of merging tip to tip [21], resulting in a curved, "hookshaped" path.…”
mentioning
confidence: 99%
“…Part c shows the statistical analysis of the fracture pattern. The number of sides for each domain of the fracture pattern shows clear peaks for the four sided domains, which is characteristic of hierarchical fracture patterns (Bohn et al, 2005). Triple junctions were found to comprise as much as 89.0% of the total junctions in the network.…”
Section: Weatheringmentioning
confidence: 95%
“…In such patterns fracture angles close to 90 ° and 180 ° (i.e. T-junctions) and four sided domains dominate (Bohn et al, 2005). The size distribution of unfractured domains also follows a log normal distribution (Iyer et al, 2008;Plümper et al, 2012).…”
Section: It Is Very Nice That the Computer Understands The Problem Bmentioning
confidence: 98%
See 1 more Smart Citation